Novel serial code concatenation strategies for error fl oor mitigation of low-density parity-check and turbo product codes - Morero, Damián Alfonso (2013)
This paper presents a novel multiple serial code concatenation (SCC) strategy to combat the error-floor problem in iterated sparse graph-based error correcting codes such as turbo product-codes (TPC) and low-density parity-check (LDPC) codes. Although SCC has been widely used in the past to reduce the error-floor in iterative decoders, the main stumbling block for its practical application in high-speed communication systems has been the need for long and complex outer codes. Alternative, short outer block codes with interleaving have been shown to provide a good tradeoff between complexity and performance. Nevertheless, their application to next-generation high-speed communication systems is still a major challenge as a result of the careful design of long complex interleavers needed to meet the requirements of these applications. The SCC scheme proposed in this work is based on the use of short outer block codes. Departing from techniques used in previous proposals, the long outer code and interleaver are replaced by a simple block code combined with a novel encoding/decoding strategy. This allows the proposed SCC to provide a better tradeoff between performance and complexity than previous techniques. Several application examples showing the benefits of the proposed SCC are described. Particularly, a new coding scheme suitable for high-speed optical communication is introduced.